Analytic Hierarchy Process in Risk Assessment: A Bibliometric Perspective - Faradillah Febriyanti; Inggit Istani Putri; Muhammad Eko Wahyudi; Putri Nandira; Queen Firakirana Ramadhani; Via Zahwa Niagara; Lusiana Desy Ariswati; Muhammad Ramadhani Kesuma (Indo Publishing, 2026)
This study analyses the development of research on the application of the Analytic Hierarchy Process (AHP) in risk assessment through a bibliometric approach. Data were collected from the Scopus database using relevant keyword combinations, yielding 1,685 articles. Analysis was conducted using VOSviewer to examine publication trends, author collaboration networks, and keyword co-occurrence patterns. The findings reveal that AHP in risk assessment has experienced significant growth and exhibits a high degree of international collaboration. The most frequently occurring keywords include